2022
DOI: 10.3390/ijerph191811565
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Colleague Suicide and the Current State of Postvention Guidance for Affected Co-Workers: A Critical Integrative Review

Abstract: People bereaved by suicide are affected psychologically and physically and may be at greater risk of taking their own lives. Whilst researchers have explored the impact of suicide on family members and friends, the area of colleague suicide has been neglected and postvention guidance for supporting surviving colleagues is often poorly developed. This critical integrative review explored the impact of colleague suicide on surviving co-workers and reviewed postvention guidance for workplaces. Systematic searches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 75 publications
(138 reference statements)
0
3
0
Order By: Relevance
“…In a systematic review of grief reactions comparing bereavement by suicide with other causes of death, those with a loss to suicide reported higher levels of rejection, shame, stigma, need for concealing the cause of death and [self] blaming than all other groups [36]. This complex response has also been cited in research on the impact of the death of a colleague by suicide [37] and amongst psychiatrists and psychologists following the death of a patient by suicide [38].…”
Section: Discussionmentioning
confidence: 93%
“…In a systematic review of grief reactions comparing bereavement by suicide with other causes of death, those with a loss to suicide reported higher levels of rejection, shame, stigma, need for concealing the cause of death and [self] blaming than all other groups [36]. This complex response has also been cited in research on the impact of the death of a colleague by suicide [37] and amongst psychiatrists and psychologists following the death of a patient by suicide [38].…”
Section: Discussionmentioning
confidence: 93%
“…Both health and mental health professionals are at risk of losing a client or a colleague to suicide. The integrated review of 17 articles conducted by Causer and colleagues [ 26 ] emphasized the impact that a suicide by a colleague may have on workers in healthcare and other settings. They found that the perceptions of grief are complicated by professional identities and workplace cultures.…”
Section: Impact Of Suicide On Mental Health Professionalsmentioning
confidence: 99%
“…This includes addressing the issue of suicide and promoting mental health and well-being. Moreover, the loss of an employee to suicide can have a profound impact on the morale and productivity of the remaining staff, leading to increased absenteeism, decreased motivation, and decreased productivity [ 10 ]. Therefore, preventing suicide is important for organizations to support the well-being of their employees, fulfil their legal and ethical responsibilities, and maintain a healthy and productive workplace.…”
Section: Introductionmentioning
confidence: 99%